Raindrops — English Language Learning Kit - Nikalje, Varada (THE PRIMARY TEACHER, 2016)
Various research studies suggest that children, particularly, in the early years, can learn best through environment and daily life activities in a stress-free atmosphere. When learning is seen as a fun activity through games and stories, children enjoy as they learn. The National Council of Educational Research and Training (NCERT), an apex body that works for school education in India, specifically, developing textbooks, supplementary reading material and e-content, has brought out a number of educational kits over the years. ‘Raindrops’ is one such kit developed for English language learning at the primary stage. The Kit aims to improve English listening and speaking skills of children in their early years in a stress-free environment and encourage construction of meaning (no rote memorisation). It also tries to sensitise sighted children to the different way of learning being done by their visually challenged peers. The Kit, therefore, helps young learners overcome their phobia for English as a difficult language. The author highlights the need to make English language a comprehensive and engaging experience for children and that educators try to move away from the conventional textbook culture, in which only the receptive capacity of children’s learning is observed and evaluated.